The Relationship Between Peak Expiratory Flow Values and The Quality of Life among Asthma Patients - Rico Irwan Saputro; R. Endro Sulistyono; Achmad Kusyairi (KHD Production, 2025)
Asthma is a common respiratory disease that significantly impacts patients' quality of life. Despite advances in asthma management, challenges remain in controlling symptoms and maintaining patients' quality of life. Peak Expiratory Flow (PEF) is an important parameter for monitoring lung function and managing asthma effectively. This study explores the relationship between Peak Expiratory Flow (PEF) values and the quality of life of asthma patients at the Pulmonary Polyclinic of Bhayangkara Lumajang Hospital. The study design used was observational analytics with a cross-sectional approach. The study population consisted of asthma patients undergoing regular check-ups at the pulmonary clinic, with a sample size of 60 patients selected through accidental sampling. Data were collected using a peak flow meter to measure PEF values and the Standardized Asthma Quality of Life Questionnaire (AQLQ-S) to assess patients' quality of life. Data analysis was conducted using the Spearman rank correlation test. The results showed that 37 respondents (61.7%) experienced airway narrowing, while 23 respondents (38.3%) had more severe airway narrowing. Regarding quality of life, 34 respondents (56.7%) fell into the moderate quality of life category, while 26 respondents (43.3%) were in the poor quality of life category. Spearman rank correlation analysis revealed a significant relationship between PEF values and the quality of life of asthma patients, with a ρ-value = 0.000. This indicates that higher PEF values are associated with better quality of life among asthma patients. The study concludes that PEF is an important indicator for assessing the quality of life of asthma patients, and regular PEF monitoring can help improve their quality of life. This research provides a foundation for developing more effective asthma management strategies.